ANALISIS MINAT SISWA TERHADAP PEMBELAJARAN DI SDN KADUBUNGBANG 1 - Neli Nurmala; Encep Supriatna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to analyze students' interest in learning at SDN Kadubungbang 1 using a descriptive qualitative approach. Data collection was carried out through observation, interviews and documentation to explore the factors that influence student interest. The research results show that student interest increases when learning uses varied methods, interactive media, and involves creative activities such as group projects or the use of teaching aids. On the other hand, monotonous learning methods such as lectures tend to reduce students' interest in learning. The role of the teacher is also an important factor, where a supportive and interactive approach is proven to be effective in generating motivation to learn. Apart from that, a conducive learning environment also supports student involvement in learning. The conclusions of this research indicate the need to implement learning strategies that are innovative, relevant and oriented towards student interests to improve the quality of learning.